Serum profiling of the antibody response to HPV in women with or without abnormal cervical cytology undergoing cervical cancer screening - Ewaisha, Radwa; Ruffin, Mack T.; Williams, Stacy; Chung, Yunro; DeGraffinreid, Cecilia R.; Paskett, Electra D.; Reiter, Paul L.; Qiu, Ji; Brenner, Dean E.; Anderson, Karen S. (Frontiers in Immunology, 2025)
IntroductionUnderstanding the humoral immune response to HPV is important for understanding the natural history of infection and developing biomarkers for early detection of cervical cancer. This has been technically limited by HPV type diversity and challenges of high-throughput protein expression and display. This study aimed to profile the humoral immune response to the proteomes of 12 HPV types in women with or without abnormal cervical cytology undergoing cervical cancer screening.MethodsTo detect serum antibodies (Abs) against HPV, we developed custom HPV high-density diffusion-free nucleic acid programmable protein arrays (HD-NAPPA) displaying the proteomes of 2 low-risk (HPV6 and 11) and 10 high-risk (HR) HPV types (HPV16, 18, 31, 33, 35, 39, 45, 51, 52 and 58). Arrays were probed with sera from women undergoing screening for cervical cancer, with normal (n=82) or abnormal (n=54) cervical cytology. HPV DNA testing and typing were done on cytology samples from all participants using an assay that detects 37 HPV types.ResultsAbs to any HPV protein were detected in 47.6% (95% C.I.: 36.5-58.8%) and 40.7% (95% C.I.: 27.9-54.9%) of women with normal and abnormal cytology, respectively and in 44.9% (95% C.I.: 36.4-53.6%) of all women. HPV16 DNA was the most frequently detected type (36.8%, 95% C.I.: 27.4-47.4%), however, Abs against HPV16 were remarkably the least frequently detected (7.4%, 95% C.I.: 3.8-13.5%). The most frequently detected Abs were against L1, in 30.1% (95% C.I.: 22.7-38.7%) of all women (31.7% and 27.8% of women with normal and abnormal Pap, respectively). Abs against E1 and E4 were the most (in 24.3%, 95% C.I.: 17.5-32.5%) and least (13.2%, 95% C.I.: 8.2-20.4%) frequently detected E-Abs in all women, respectively. Among all subjects with antibodies to either L1 or L2, 39.0% (95% C.I.: 24.6-55.5%) of those with L1 antibodies and 51.9% (95% C.I.: 32.4-70.8%) of those with L2 antibodies were positive for the antigen from only one HPV type.ConclusionOur findings shed light on the kinetics of HPV-specific humoral immunity in women with normal or abnormal cervical cytology and highlight the need for comprehensive immune profiling in different health and disease stages.